Sociocultural perceptions of physical activity and dietary habits for hypertension control: voices from adults in a rural sub-district of South Africa - Kganetso Sekome; Francesc Xavier Gómez-Olivé; Lauren B. Sherar; Dale W. Esliger; Hellen Myezwa (BMC, 2024)
Abstract Background Over half of adults from rural South Africa are hypertensive. Apart from pharmaceutical treatment, lifestyle changes such as increasing physical activity and reducing dietary salt have been strongly advocated for the control of hypertension. However, the control rates of hypertension for adults in rural South Africa are low. In this paper we explore whether this is due to the recommended lifestyle intervention not aligning with the individual's socio-cultural determinants of behaviour change. Aim To explore the social and cultural beliefs, perceptions and practices regarding physical activity and diet as a hypertension control intervention on hypertensive adults living in a rural sub-district in South Africa. Methods Nine focus group discussions were conducted with hypertensive adults aged 40 years and above from Bushbuckridge sub-district in Mpumalanga Province of South Africa using a semi-structured interview guide. Each session began with introductions of the discussion theme followed by a short discussion on what the participants know about hypertension and the normal blood pressure readings. Physical activity and dietary habits were then introduced as the main subject of discussion. Probing questions were used to get more insight on a specific topic. A thematic analysis approach was used to generate codes, categories, and themes. A manual approach to data analysis was chosen and data obtained through transcripts were analysed inductively. Findings Participants had a lack of knowledge about blood pressure normal values. Perceived causes of hypertension were alluded to psychosocial factors such as family and emotional-related issues. Physical activity practices were influenced by family and community members' attitudes and gender roles. Factors which influenced dietary practices mainly involved affordability and availability of food. To control their hypertension, participants recommend eating certain foods, emotional control, taking medication, exercising, praying, correct food preparation, and performing house chores. Conclusion Lifestyle interventions to control hypertension for adults in a rural South African setting using physical activity promotion and dietary control must consider the beliefs related to hypertension control of this population.